Answer:
[tex]f(x) = x^4-5x^2+3[/tex] is symmetric to the y-axis
Step-by-step explanation:
Given
[tex]f(x) = x^4-5x^2+3[/tex]
Required
Determine if it is symmetric
First, we check if the function is even by calculating f(-x)
[tex]f(x) = x^4-5x^2+3[/tex]
[tex]f(-x) = (-x)^4-5*(-x)^2+3[/tex]
[tex]f(-x) = x^4-5*x^2+3[/tex]
We have:
[tex]f(x) = f(-x) = x^4-5*x^2+3[/tex]
This implies that the function is even, and even functions are symmetric to the y-axis.
Hence:
[tex]f(x) = x^4-5x^2+3[/tex] is symmetric to the y-axis